2020
DOI: 10.1186/s13741-020-00166-0
|View full text |Cite
|
Sign up to set email alerts
|

Can technology optimise the pre-operative pathway for elective hip and knee replacement surgery: a qualitative study

Abstract: Background An ageing population has resulted in a rise in the number of hip and knee replacement surgeries in the UK. The pre-operative pathway is plagued with issues causing long delays and cancellations. Virtual healthcare technologies have a growing evidence base to help solve these issues. One problem of implementing these technologies is the resistance to change mentality from healthcare professionals. By getting their opinions on the place of these technologies within the pre-operative pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In this context, research has focused on the orthopedic clinician's use of digital technologies [1,17], for instance, in supporting their educational development [18], guiding clinical decision support [19], managing care referrals [20], and building the patient-clinician relationship [21,22]. Recognizing and understanding the potential unmet needs of elective orthopedic surgery patients is central to motivating healthier behavior change, improving their recovery, and optimizing overall surgical success in the short and long term [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, research has focused on the orthopedic clinician's use of digital technologies [1,17], for instance, in supporting their educational development [18], guiding clinical decision support [19], managing care referrals [20], and building the patient-clinician relationship [21,22]. Recognizing and understanding the potential unmet needs of elective orthopedic surgery patients is central to motivating healthier behavior change, improving their recovery, and optimizing overall surgical success in the short and long term [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review provides moderate evidence prehabilitation improves patient outcomes when undergoing elective THR surgery 21-23 and strong evidence virtual services are effective, feasible, and acceptable to patients. 20-22,25,26…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, three participants did not recommend pre-operative physiotherapy because they did not find it helpful or felt that the same exercises could be obtained online [75]. In a qualitative study by Sharif et al [84], health professionals identified that web-based written information, mobile health, and remote monitoring technologies could play a role in pre-operative exercise provision, encouragement, and/or monitoring.…”
Section: Views Studiesmentioning
confidence: 99%
“…Furthermore, the COVID-19 pandemic has highlighted the need for remote models of care [104,105]. Using digital tools to deliver TKR care remotely offers multiple potential benefits, such as improved service efficiency and greater patient engagement [84,104]. Conversely, this review identified few studies that investigated the effectiveness of digital tools.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%